Apache essentials : install, configure, maintain - Harkness, Darren James (ITpro collection, 2022)
Take a friendly, non-technical approach to installing, configuring, and maintaining a web server for development and testing on Mac OS, Linux, and Windows. This new edition uses straightforward language to demystify the mechanics of the web, leading the reader through a complex topic via simple, iterative steps. The book reflects current, relevant Apache configurations and web application frameworks, and prepares the reader for working in professional web development environments. You'll begin by reviewing a brief history of Apache that focuses on the necessary foundation to understand what these web servers are and why they are used. You'll then install a basic Apache setup on your operating system that loads a static HTML file for display in a browser. Next you'll work through progressively more detailed configurations towards a modern, secure application development environment for the two most commonly implemented development frameworks: a PHP-based framework such as Laravel or a NodeJS application. In the end, Apache Essentials, second edition will show novice web developers and UX professionals how to quickly and confidently build and test their website changes safely and securely.